Progress in reducing premature mortality from cancer and cardiovascular disease in the former Soviet Union, 2000–19. (20th April 2022) - Znaor, Ariana; Corbex, Marilys; Cao, Bochen; Laversanne, Mathieu; Ryzhov, Anton; Smelov, Vitaly; Bray, Freddie
Abstract: Background: A reduction in non-communicable diseases premature mortality by one-third by 2030 is one of the targets of the UN Sustainable Development Goals (SDG3.4). We examined the mortality profiles in the Newly Independent States of the former Soviet Union (NIS) and the European Union (EU) and assessed progress in reductions of premature mortality from cancer, as compared to cardiovascular disease (CVD). Methods: We used WHO's Global Health Estimates and GLOBOCAN 2020 to examine current mortality profiles and computed the unconditional probabilities of dying at ages 30–70 from CVD and cancer for the years 2000–19 in both sexes, using a linear extrapolation of this trend to predict whether the target of a one-third reduction, as set in 2015, would be met in 2030. Results: CVD was the main cause of premature death in the NIS (43%), followed by cancer (23%), inversely from the EU with 42% cancer and 24% CVD deaths. The NIS achieved major reductions in premature CVD mortality, although the probabilities of death in 2019 remained about five times higher in the NIS compared to the EU. For cancer, mortality reductions in most NIS were quite modest, other than large declines seen in Kazakhstan (44%) and Kyrgyzstan (30%), with both on course to meet the 2030 target. Conclusions: Limited progress in cancer control in the NIS calls for policy action both in terms of structural changes towards universal health coverage, and scaling up of national cancer control plans, including a shift from opportunistic to evidence-based early detection practices.